Violence against women in Egypt: Public policies and services - Rateb, Maha Said (AUC Knowledge Fountain, 2017)
Violence against women is one of the main forms of gender based discrimination that is prevalent in several countries. On the global level, Egypt is committed to international conventions and declarations to combat different forms of violence against women such as the Convention of the Elimination of Discrimination against Women (CEDAW) and Beijing declaration. Nationally, the Egyptian constitution mentions that the state is committed to address violence against women and a national strategy was developed two years ago to support the issue. However, the issue is still prevalent in Egypt and several news articles have been reporting on different cases of violence against women happening across a number of governorates. Based on a recent study published by the National Council for Women, CAPMAS and with the support of UNFPA, “Around 30 percent of women age 18-64 have been exposed during the past 12 months to at least one act of violence perpetrated by any of the three categories of perpetrators: spouse/fiancé, other close individuals or strangers in private and public spaces” (UNFPA, 2015, p.120). This research paper focuses on the policies and services offered by the Egyptian state to females survivors of violence and to what extent these policies are responsive and effective. Various studies have examined the state’s response to violence against women in different countries. Nonetheless, the studies conducted on violence against women in Egypt did not discuss the national efforts to solve the issue and create a better environment for Egyptian women. Through applying a qualitative approach, this research concluded that there are a number of policies and services either formulated or implemented to address the issue in Egypt. However, the findings highlighted that there are remarkable gaps in the responsiveness and effectiveness of these policies and services. In other words, the objectives of these policies and services are not successfully met. In addition, their responsiveness in terms of addressing the needs of the female survivors of violence in Egypt is being questioned. Accordingly, a number of policy recommendations are highlighted at the end of the study based on the findings reached.